Quantifying the effect of polynuclear hydroxocomplex adsorption on the charge reversals at solid surfaces. Issue 2 (April 2022) - Raji, Foad; Nguyen, Cuong V.; Nguyen, Anh V.
Abstract: The adsorption of heavy metal ions onto negatively charged oxide (quartz) surface in environmental settings produces three surface charge reversals (CRs) described as CR1 at low pH, CR2 at middle pH, and CR3 at high pH. The available physical quantitative approaches cannot predict all these CRs and are not applicable for low salt concentrations (< 1 mM). In this study, a new model was presented to describe the CRs of the Pb(II)-quartz system by combining the ion distribution as the inner- and outer-sphere complexes within the compact (Stern) layer of the electrical double layer theory and the adsorption of Pb(II) hydroxocomplexes by the surface complexation and precipitation. The results indicated that the model agreed with the measured surface (zeta) potential values and the observed CRs for quartz particles in Pb(II) solutions over a wide range of Pb(II) concentrations, pH, and solution ionic strength. The model showed the pivotal role of Pb(II) polynuclear hydroxocomplexes (PNHCs) such as P b 3 OH 4 2 + in the appearance of the CR2. The predicted surface binding constants for PNHCs were lower than their corresponding hydrolysis constants which implied an earlier formation of those species at the interface than in the bulk solution. Increasing the solution ionic strength reduced the magnitude of surface potential and shifted the CR2 to higher pH values. The model was also validated with the literature data. With better understanding the role of PNHCs sorption and CR mechanisms, this model may also be adapted to other systems containing multivalent ions that are relevant to environmental applications. Graphical Abstract: ga1 Highlights: Developing a surface complexation model for surface charge reversals (CRs). Pivotal role of polynuclear hydroxo complexes in predicting middle-pH CR. Predicting high-pH CR requires the addition of surface precipitation reaction. Inner-sphere surface complexation dominates Pb(II) sorption onto quartz surface.